Are High-Interest Loans Predatory? Theory and Evidence from Payday Lending - Allcott, Hunt; Kim, Joshua; Taubinsky, Dmitry; Zinman, Jonathan (Review of Economic Studies, 2022)
Abstract It is often argued that people might take on too much high-cost debt because they are present focused and/or over-optimistic about how soon they will repay. We measure borrowers’ present focus and over-optimism using an experiment with a large payday lender. Although the most inexperienced quartile of borrowers under-estimate their likelihood of future borrowing, the more experienced three quartiles predict correctly on average. This finding contrasts sharply with priors we elicited from 103 payday lending and behavioural economics experts, who believed that the average borrower would be highly overoptimistic about getting out of debt. Borrowers are willing to pay a significant premium for an experimental incentive to avoid future borrowing, which we show implies that they perceive themselves to be time inconsistent. We use borrowers’ predicted behaviour and valuation of the experimental incentive to estimate a model of present focus and naivete. We then use the model to study common payday lending regulations. In our model, banning payday loans reduces welfare relative to existing regulation, while limits on repeat borrowing might increase welfare by inducing faster repayment that is more consistent with long-run preferences.